A Gadget Recommendation System using Data Science (Journal of Information Technology and Digital World, 2020)
Electronic gadgets have become vital in basic need of individual. The advances in technology, makes it necessary to satisfy different functional needs of users. Therefore, it is important to suggest gadgets for users according to personal preference and various constraints of electronic gadgets. We propose a gadget recommendation system by integrating various requirements from users.
Keywords: Gadget recommendation; classification; model rendering; k-means algorithm; content-based filtering